The Effect of Entomopathogenic Fungi Combinations on the Growth and Production of Corn ( Zea mays L.) - Indri Yanil Vajri VAJRI; Trizelia; Haliatur Rahma; Yusniwati (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Entomopathogenic fungi (CEPs) possess dual potential as biological control agents and endophytes that modulate plant physiological processes. Single applications of CEPs often provide suboptimal protection and growth support, necessitating a synergistic, interspecies combination approach. This study aimed to evaluate the effects of single and combined inoculations of CEPs on the growth, chlorophyll content, and yield components of shelled corn (Zea mays L.). A Randomized Block Design (RBD) with eight treatments and four replications was employed. The treatments included Beauveria bassiana (BBWS), Metarhizium anisopliae (B22C), and Trichoderma asperellum (A116), applied singly or in combination via seed soaking for six hours. Sterile distilled water served as the control. Observed parameters included plant growth, leaf chlorophyll content, and yield components. Data were analyzed using Analysis of Variance (ANOVA), followed by the Least Significant Difference (LSD) test at the 5% significance level. Results indicated that fungal inoculation had no significant effect on corn vegetative growth six weeks after planting. However, the combination of B. bassiana and M. anisopliae produced the highest total chlorophyll content (1,101 μg g⁻¹), whereas single inoculations decreased chlorophyll levels, likely due to carbon costs during the initial phase of endophyte colonization. Importantly, the combination of M. anisopliae and T. asperellum yielded the highest number of kernels per ear, ear weight, and 100-kernel weight. This research advances previous studies by demonstrating that synergistic fungal combinations effectively mitigate early-phase carbon costs, thereby maximizing crop yields compared to single applications. Therefore, the combination of M. anisopliae and T. asperellum is recommended as a biofertilizer formula and biocontrol agent for sustainable corn kernel production.